Analisis Kinerja Online Shop dalam Upaya Meningkatkan Penjualan Produk Muslimah di Marichashop Bekasi: Analisis Kinerja Online Shop dalam Upaya Meningkatkan Penjualan Produk Muslimah di Marichashop Bekasi - Fauziah, Neng Hilda; Tiris Sudrartono, Tiris Sudrartono (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research was conducted to determine the performance of online shops at Marichashop Bekasi Stores in finding solutions and efforts that can be made to increase product sales using marketing mix strategies. Qualitative method with descriptive data analysis using the results of interviews with Marichashop Store owners to find out the details of the problems being faced and the author's views regarding marketing mix strategies in an effort to increase product sales at Marichashop Bekasi Store. The results showed that Marichashop did not carry out the performance process optimally, it was because Marichashop was still carrying out a conventional performance process where Marichashop only used WhatsApp media as a communication and promotion tool in selling. Selling with a distribution system and not utilizing the development of information technology now such as social media and marketplaces well. That caused sales for the last 1 year to fluctuate, even in May it experienced a significant decline of 85.45%. With that, you must consistently carry out a marketing mix strategy and adapt to the development of information technology. Mainly marketplaces and social media by creating Marichashop accounts, both social media accounts and marketplaces and using them as promotional media.